PENERAPAN KEBIJAKAN PENGELOLAAN LINGKUNGAN MENUJU UDARA BERSIH DI KERAJINAN PERAK DESA CELUK PROVINSI BALI - Arian Pramudi (Program Studi Manajemen Lingkungan, 2020)
The village of Celuk belongs to Sukawati sub-district, Gianyar regency of Bali province. Celuk Bali Village is famous for the results of gold and silver craftsmen, the home-made crafts do have the quality and taste of high-value art. Silvery handicraft activity one of them is the activity of plating (elektoplating). Electroplating process in addition to producing useful products, also produce solid waste, gas and liquid emissions. Waste in the form of gas emissions generally comes from the evaporation of electrolyte, solvent, acid vapor, and cleaning fluids. The purpose of this paper is how the implementation of environmental management policy of air pollution control towards clean air to silver artisans in Celuk Village. By using methods of data collection with instruments and interviews. From the results of questionnaires and interviews, 0% results obtained for indicators of the implementation of environmental management policies of air pollution control and only 25% for the indicator of clean air